Undoing ableism: disability as a category of historical and legal analysis - Beckmann, Lisa; Justus Liebig University Giessen (My University, 2017)
In this essay, I will apply disability as a category of legal and historical analysis to undo the different forms ableism can take in US history and law. My aim is to look at a specific time period in US history the turn from the nineteenth to the twentieth century in order to elucidate narratives of exclusion and marginalization of disabled people on the one hand and resistance and resilience on the other. My claim is that in this period, disability gains particular political and legal relevance as an intersectional, i.e. a gendered, classed, and racialized category of analysis, which leads to the cross-connection between ableism and other dominant ideologies, such as sexism, racism, and classism.In order to give my analysis historical and cultural specificity, I will look at two distinct historical and legal contexts. In the first part of this essay, I discuss the inter-relation of ableism and classism in the context of the industrialization and the subse-quent socioeconomic discrimination of disabled factory workers. As a legal subtext, the fellow servant rule will be discussed to understand how this particular law be-comes relevant for disability politics.In the second part of the essay, ableism is explored in the context of racism to understand how atavism and biological determinism contributed to the othering of disabled people, especially disabled women, in the context of eugenic ideology of the early twentieth century. Here I will discuss the US Supreme Court decision for the case Buck v. Bell in order to understand eugenic law as a reflection of an ideology that is both ableist and sexist at its core.
Keywords: disability history; Disability Studies; disability law; eugenics; industrialization; ddc:300